The official Harry Potter baking book / 40+ Recipes Inspired by the Films - Farrow, Joanna (New York, NY : Scholastic Inc., 2021)
This one-and-only official Harry Potter cookbook offers 43 delicious recipes that include Pumpkin Patch pies, Owl muffins, and Hogwarts gingerbread, and provides gluten-free, vegetarian, and vegan options as well.
"Wizarding world."
Includes index.
Keywords: Baking -- Juvenile literature; Harry Potter films -- Miscellanea -- Juvenile literature; Baking; Harry Potter films -- Miscellanea; Cookbooks; Cookbooks